Validation of 3-Minute Nutrition Screening-Paediatric (Paediatric 3-MinNS) for Hospitalized Children. Issue 2 (April 2021) - Yeo, Pei Sien; Boey, Christopher Chiong Meng; Lim, Su Lin; Abdul Majid, Hazreen
Abstract : Nutrition screening in pediatric hospitals is not a common practice in many countries. This study validated the 3-Minute Nutrition Screening-Paediatric (Paediatric 3-MinNS) with Screening Tool for the Assessment of Malnutrition in Paediatrics (STAMP), anthropometric measures, biochemical parameters, and dietary assessment. This cross-sectional study included 165 patients aged 2 to 12 years admitted as pediatric patients to the University Malaya Medical Centre. The tool identified 26.1% of patients as being at high risk of malnutrition. The findings suggest that Paediatric 3-MinNS offers a valid and reliable screening tool for early recognition of children at risk of malnutrition.